Стереотипізація ісламу в мас-медіа - Бутиріна, М. (Відділення релігієзнавства Інституту філософії ім. Г.С. Сковороди НАН України, 2010)
У статті Бутиріної М.В. «Стереотипізація ісламу у мас-медіа» висвітлюються особливості мас-медійної стереотипізації ісламу. Актуалізуються питання формування та функціонування етнорелігійних стереотипів. Ключові слова: етнорелігійні стереотипи, мас-медіа, іслам, релігія, національна ідентичність. В статье Бутыриной М.В. «Стереотипизация ислама в масс-медиа» освещаются особенности масс-медийной стереотипизации ислама. Актуализируются вопросы формирования и функционирования этнорелигиозных стереотипов. Ключевые слова: этнорелигиозные стереотипы, масс-медиа, ислам, религия, национальная идентичность. The problem of mass media stereotype formation of Islamic theme is under study in the thesis by M.Butyrina “Stereotyping of Islam in Mass-media”. The factors and conditions of ethnical and religious stereotype formation are researched here. Key-words: ethnic and religious stereotypes, mass-media, religion, Islam, national identity.